A Study of Big Data in Cloud Computing - Imran Khan (Computer assisted methods in engineering and science, 2024)
Over the last two decades, the size and amount of data has increased enormously, which has changed traditional methods of data management and introduced two new technological terms: big data and cloud computing. Addressing big data, characterized by massive volume, high velocity and variety, is quite challenging as it requires large computational infrastructure to store, process and analyze it. A reliable technique to carry out sophisticated and enormous data processing has emerged in the form of cloud computing because it eliminates the need to manage advanced hardware and software, and offers various services to users. Presently, big data and cloud computing are gaining significant interest among academia as well as in industrial research. In this review, we introduce various characteristics, applications and challenges of big data and cloud computing. We provide a brief overview of different platforms that are available to handle big data, including their critical analysis based on different parameters. We also discuss the correlation between big data and cloud computing. We focus on the life cycle of big data and its vital analysis applications in various fields and domains At the end, we present the open research issues that still need to be addressed and give some pointers to future scholars in the fields of big data and cloud computing.